Degradation of organophosphate esters in sewage sludge: Effects of aerobic/anaerobic treatments and bacterial community compositions. (May 2018) - Pang, Long; Ge, Liming; Yang, Peijie; He, Han; Zhang, Hongzhong
Highlights: The biodegradation of OPEs under aerobic/anaerobic condition was studied. The addition of pig manure enhanced the degradation of OPEs. The abundance and diversity of bacterial communities reduced after the treatment. Five genera might be responsible for the biodegradation of OPEs. Abstract: In this study, the degradation of organophosphate esters (OPEs) in sewage sludge with aerobic composting and anaerobic digestion was investigated. The total concentrations of six OPEs (ΣOPEs) in the whole treatment process reduced in the order of anaerobic digestion combined with pig manure (T3) > aerobic composting combined with pig manure (T1) > aerobic composting (T2) > anaerobic digestion (T4). The addition of pig manure significantly enhanced the removal rate of OPEs in both aerobic and anaerobic treatments. The abundance and diversity of bacterial community reduced after the treatment process. Shannon index, principal component analysis, network analysis, and heat map further confirmed the variation of bacterial community compositions among different treatments. Five genera (i.e., Flavobacterium, Bacillus, Alcaligene, Pseudomonas, and Bacillus megaterium ) might be responsible for the degradation of OPE compounds in sewage sludge.